(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Customers who are technologically aware depend heavily on social media sites to learn about, comprehend, and create opinions on products. These social media organizations employ a variety of strategies to draw customers and keep them interested in their media postings, including photographs, videos, blogger reviews, shop reviews, after-purchase feedback etc. Social media platforms are regarded as a one-stop shop where both customers and sellers carry out a variety of marketing strategies. Everything from product search to product reviews to post-purchase reviews occurs on a single social media platform, with spillover effect on other social media platforms. This article aimed to assess the influence of customer engagement in social media on the purchase behaviour of customers in Kerala. The study found that customer engagement practices followed by the social media sites differ from one to another